2012
DOI: 10.2320/matertrans.m2011263
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Black Ceramic Layer on Aluminum Alloy by Plasma Electrolytic Oxidation in Electrolyte Containing Na<sub>2</sub>WO<sub>4</sub>

Abstract: The formation of black ceramic layer produced by plasma electrolytic oxidation (PEO) coating has been investigated as a function of coating time. A series of PEO coatings was carried out on aluminum alloy sample in a phosphate electrolyte containing sodium tungstate (Na 2 WO 4 ) with four different coating times, i.e., 20, 100, 200 and 300 s. As the coating time increased, the amount of tungsten element in the ceramic layer increased, resulting in the black ceramic layer. This phenomenon was discussed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Among the colored coatings, the black coatings with high emissivity and high absorption are highly desired for the interior components of airships, especially for electronics house packaging for thermal control applications 42–44 . Salts of transition metals such as V and W are usually used as additives to fabricate black PEO coatings 42,45,46 . However, the alloying elements from substrate metal may also play a role on the color of the PEO coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the colored coatings, the black coatings with high emissivity and high absorption are highly desired for the interior components of airships, especially for electronics house packaging for thermal control applications 42–44 . Salts of transition metals such as V and W are usually used as additives to fabricate black PEO coatings 42,45,46 . However, the alloying elements from substrate metal may also play a role on the color of the PEO coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Salts of transition metals such as V and W are usually used as additives to fabricate black PEO coatings. 42,45,46 However, the alloying elements from substrate metal may also play a role on the color of the PEO coatings. Han et al 12 demonstrated that the oxidation of titanium substrate into low-valence oxides of titanium (Ti 2+ , Ti 3+ ) leads to black coatings.…”
Section: Introductionmentioning
confidence: 99%
“…For Al alloys, Li et al [19] prepared a black MAO film on the LY12 Al alloy derived from the silicate electrolyte embracing NH 4 VO 3 . Hwang and Shin [20] obtained a sort of black film by adding Na 2 WO 4 into the phosphate electrolyte. Wang and Nie [21] invented a new blue plasma electrolytic oxidation film on wrought 2024 Al alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature on plasma electrolytic oxidation (PEO), coloring the valve metal surface has been performed through adding either soluble metal salts or suspended pigments in the electrolytic solution. We prefer pigment to metal salt since the pigment is more manageable in industrial practice.…”
Section: Introductionmentioning
confidence: 99%